Avaliação da influência da redução das temperaturas de usinagem e de compactação no comportamento mecânico de misturas asfálticas mornas - Wargha Filho, Nelson (2013)
The reduction in mixing and compaction temperatures of asphalt mixtures is considered an alternative for the production of asphalt pavements and can offer technical economical and environmental advantages. Several technologies are used in the production of these mixtures usually called warm mix asphalt (WMA). This research aimed to compare some of these technologies with a hot mix asphalt produced at the temperature obtained from the commonly used viscosity versus temperature curve. The binder used was the AC classified by penetration as AC 50-70. The so called "Control mix" refers to the mix that was no was (binder and / or production process) while the other two mixtures studied were produced by modifying the original AC 50-70 with two different additives. A 4th mixture was produced with 2% moisture. Thus, the mixtures studied were distributed as follows: (i) Pure AC; (ii) AC with commercial surfactant additive known as Gemul®; (iii) AC with carnauba wax CT4; (iv) Pure AC with moist aggregates. The binders and the aggregates were characterized according to current Brazilian specifications. To provide greater resistance to permanent deformation especially during compaction the Bailey methodology was used to generate the gradation curve. Thus, more interlocking between the aggregates was expected. The compaction temperature of the specimens was determined by CDI and TDIm parameters, seeking to obtain similar workability to the control mixture and that simultaneously show themselves in appropriate conditions to resist permanent deformation. These parameters (CDI and TDIm) are calculated from output data from the gyratory compactor, and for this reason the Superpave design method was used. To evaluate the effect of temperature reduction and different additives on mechanical properties, tests related to mixture permanent deformation, stiffness and sensitivity to moisture damage were performed. After comparison and analysis of the mechanical tests, an assessment of costs of each mixture was performed to evaluate the economic viability of the studied samples. It can be said that all modified mixtures behaved in a similar manner to the mixture produced with no modification in the binder or in mix/compaction temperature. It is attempted to perform a cost assessment of each mixture in order to evaluate the economic viability. As expected, the mixture with moist aggregate had the lowest value, for not having used additive and due to temperature reduction. The mixture with the additive Gemul® had almost the same cost of the control mixture, while the mixture with wax CT4 had the cost increased by about 6% compared to the Control mixture. It is expected this research along with others already published in Brazil can demonstrate that WMA not only contributes to the environmental damage mitigation, but also presents technical and economic advantages and, therefore it is a technique that can be used in this country to be produced